2006
DOI: 10.1093/annonc/mdl135
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity and health-related quality of life in breast cancer patients receiving adjuvant docetaxel, doxorubicin, cyclophosphamide (TAC) or 5-fluorouracil, doxorubicin and cyclophosphamide (FAC): impact of adding primary prophylactic granulocyte-colony stimulating factor to the TAC regimen

Abstract: The addition of PPG significantly reduces the incidence of neutropenic fever associated with TAC chemotherapy as well as that of some TAC-induced haematological and extrahaematological side-effects. The HRQoL of patients treated with TAC is worse than that of those treated with FAC but improves with the addition of PPG, particularly in the final part of chemotherapy treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
107
1
6

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 183 publications
(128 citation statements)
references
References 17 publications
14
107
1
6
Order By: Relevance
“…When comparing patients receiving docetaxel-based combination regimens, a significant reduction in the incidence of febrile neutropenia and other neutropenia-related complications was observed in patients receiving docetaxel-based combination regimens with primary prophylactic G-CSF (26,27). Recent European and American guidelines recommend the routine use of primary prophylaxis with G-CSF when using chemotherapeutic regimens associated with a risk of febrile neutropenia of ≥20%, such as DCF (28,29).…”
Section: Discussionmentioning
confidence: 99%
“…When comparing patients receiving docetaxel-based combination regimens, a significant reduction in the incidence of febrile neutropenia and other neutropenia-related complications was observed in patients receiving docetaxel-based combination regimens with primary prophylactic G-CSF (26,27). Recent European and American guidelines recommend the routine use of primary prophylaxis with G-CSF when using chemotherapeutic regimens associated with a risk of febrile neutropenia of ≥20%, such as DCF (28,29).…”
Section: Discussionmentioning
confidence: 99%
“…The base-case analysis used in this model applied a 5% discount rate, the Canadian costs for chemotherapies recommended by cco guidelines 10 , and febrile neutropenia rates based on the available tac-fac study results 17 . The incremental cost-effectiveness ratio (icer) for tac compared with fac was $6,921.24/ ly gained.…”
Section: Resultsmentioning
confidence: 99%
“…We wanted to conduct an alternative analysis looking at the cost-effectiveness of tac versus fac in the context of primary g-csf prophylaxis-that is, the administration of g-csf before the occurrence of febrile neutropenia or other documented infection. To do so, we used the geicam (Grupo Español de Investigación del Cáncer de Mama) 9805 study 17 for the costing of adverse events, because we could then compare adverse events rates with and without primary prophylaxis within the context of a single study. Because the rate of febrile neutropenia in the tac group was the major driver of adverse event costs and the variable that would be affected by g-csf prophylaxis, it is important to note that the adverse event rates for grades 3 and 4 febrile neutropenia reported in the geicam study for the pre-tac and fac groups were similar to those reported in the tac-fac study 1 .…”
Section: Cost Of Primary Prophylaxis Of Febrile Neutropenia With G-csfmentioning
confidence: 99%
“…In our study, complete clinical and pathologic response rates were significantly higher in the TAC arm. Post chemotherapy, hematologic complications can be life-threatening (21) . Prophylactic G-CSF is administered to the patients with TAC regimen.…”
Section: Discussionmentioning
confidence: 99%